Gender Identity Norms, Mental Health, and Relationship Strain - David W. Johnston; Rachel Knott; Nidhiya Menon (Institute of Labor Economics (IZA), 2025)
Although studies have evaluated the costs of violating the male breadwinner norm, little is known about the mental health consequences, particularly for common conditions such as depression and anxiety. We explore this issue using Australian national administrative tax and healthcare records. We estimate individual- and employer-level fixed models of mental health service use and prescription medication. We find that men are significantly more likely to use mental health care following periods when their wife earns more, with the strongest effects emerging two years after the earnings shift. By contrast, we find no consistent effects for women. Our results are robust to alternative specifications, including the inclusion of controls for labour market shocks, and an alternative estimation strategy based on a local linear regression discontinuity design. We find that couples are also more likely to separate following norm violations, suggesting relationship strain as a key mechanism. Complementary evidence on relationship satisfaction from Australian household survey data provide further support of this pathway. Our findings demonstrate that traditional gender identity norms impose psychosocial costs within modern households.
Keywords: D10; J12; J16; J31; J22; I10; I12; 330; relative income; mental health; medication; relationship strain; separation